Not what you expect: assortative male choice without assortative pairing pattern in a Nephila spider - Pollo, Pietro (2018)
Male mate choice occurs in species in which males face high mating costs, leading to few opportunities to copulate. Additionally, if male-male competition is strong, male mate choice should be influenced by male fighting ability. Good competitors should choose high quality females because they may be able to fight off contenders, while poor competitors should choose lower quality females. In Nephila clavipes spiders, males have limited sperm supply and fight for access to females. Here, using field experiments and observational data, we tested whether female quality and male size (a proxy of fighting ability) affect the pairing likelihood of males. In our experiments, we found that males did not express mate choice initially, but, after a few hours, chose their mates based on female size and female recent pairing status. Importantly, male mate choice direction and intensity varied with male size, as large males guarded larger females that were not recently paired and small males guarded smaller females that were recently paired. The observational data provided little evidence of assortative pairing regarding body size. With our field experiments, we show that crucial information can be collected by assessing mate choice in multiple moments. Taken together, our findings reveal the importance of considering male traits and the social context in understanding variation in male mate choice, which is often neglected in empirical studies